2022
DOI: 10.2147/jir.s366886
|View full text |Cite
|
Sign up to set email alerts
|

Carbon 60 Dissolved in Grapeseed Oil Inhibits Dextran Sodium Sulfate-Induced Experimental Colitis

Abstract: Introduction Carbon 60 (C60) and its derivatives have various biological applications. In our laboratory, we have demonstrated that C60 dissolved in grape seed oil (C60-Oil) has antioxidant and anti-inflammatory properties; however, the effectiveness of this formulation to treat diseases of the intestinal tract and specifically ulcerative colitis has not been studied. In this study, we intend to explore the effects of C60-Oil against experimental ulcerative colitis induced by Dextran Sulfate Sodiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“… 57 , 58 We used recombinant human intestinal alkaline phosphatase, known to inhibit inflammation, and carbon-60 dissolved in grape seed oil to verify the reliability of the methods in this study. 63
Figure 4 35 kDa B-HA inhibits the production of ROS and TNF-α by human neutrophils in blood vessels. ( A ) The inhibitory effects of low concentrations (40 μg/mL) of HA and 35 kDa B-HA on the production of ROS in freshly extracted human neutrophils.
…”
Section: Resultsmentioning
confidence: 99%
“… 57 , 58 We used recombinant human intestinal alkaline phosphatase, known to inhibit inflammation, and carbon-60 dissolved in grape seed oil to verify the reliability of the methods in this study. 63
Figure 4 35 kDa B-HA inhibits the production of ROS and TNF-α by human neutrophils in blood vessels. ( A ) The inhibitory effects of low concentrations (40 μg/mL) of HA and 35 kDa B-HA on the production of ROS in freshly extracted human neutrophils.
…”
Section: Resultsmentioning
confidence: 99%
“…Another study found that administering grape seed oil enema significantly improved inflammation in colitis rats [81]. In addition, grape seed oil rich in Carbon 60 significantly reduced the inflammatory response in DSS-induced colitis rats [82]. The therapeutic effect of grape seed oil on IBD is attributed to its powerful antioxidant activity.…”
Section: Grape Seed Oilmentioning
confidence: 99%
“…Previous study also suggest C-60 as a viable alternative for the treatment of allergic and inflammatory conditions [17]. Our previous study demonstrated the efficacy of orally administered fat-soluble C-60 oil in treating colitis in mice [18]. Relevant patents and additional studies have further supported the role of fat-soluble C-60 oil in colitis treatment in mice [19][20][21][22].…”
mentioning
confidence: 90%